2002
DOI: 10.1016/s0378-1097(02)00965-5
|View full text |Cite
|
Sign up to set email alerts
|

Growth pH and transient increases in amino acid availability influence polyglucose synthesis by Fusobacterium nucleatum grown in continuous culture

Abstract: Fusobacterium nucleatum is a Gram-negative anaerobe that has been implicated in the aetiology of several diseases including periodontal diseases. Like other fusobacteria, it derives energy from the fermentation of amino acids and, in resting (non-growing) cells, this enables the organism to transport glucose and synthesise intracellular polyglucose (IP). The continued availability and fermentation of amino acids inhibits IP breakdown. We have grown F. nucleatum in continuous culture in a chemically defined med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Studies have shown that at lower pH values, nicotine is less toxic. However, the increase in the concentration of nicotine in the medium may cause alkalinization and higher absorption of nicotine by the cells, and thus lead to an increase in the production of biofilm and its toxicity 50) .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that at lower pH values, nicotine is less toxic. However, the increase in the concentration of nicotine in the medium may cause alkalinization and higher absorption of nicotine by the cells, and thus lead to an increase in the production of biofilm and its toxicity 50) .…”
Section: Discussionmentioning
confidence: 99%
“…We interpret this to mean that S. aureus adapts to SCFAs by modifying its physiology rather than directly detoxifying them via degradation. The increased acetate levels are likely due to S. aureus utilization of glucose remaining in Fn CFS, as F. nucleatum preferentially ferments amino acids 20,21 . Given that S. aureus growth is similarly impaired when BB is supplemented with the sodium salts of acetate (5mM), propionate (5mM), and butyrate (15mM)(Fig.…”
Section: S Aureus Growth Is Impaired By F Nucleatummentioning
confidence: 99%
“…The continued fermentation of glutamate inhibits IP breakdown in anaerobic cultures but, as glutamate becomes depleted, IP is catabolised to a mixture of butyric, acetic, lactic and formic acids (11). In contrast to resting cells, studies on F. nucleatum growing in continuous culture at pH 7.4 (18) have shown that, at steady state, little IP is stored intracellularly when the cells are fermenting both glucose and energy‐yielding amino acids. Under these conditions, IP is metabolised and the energy derived is used to maximise cell numbers.…”
Section: The Effect Of Fructose and Energy Yielding Amino Acids On Thmentioning
confidence: 99%